High-performance liquid chromatography for analytical chemistry - Santoso, Setiyo Budi (Innovation in Health for Society, 2021)
High-performance liquid chromatography has replaced several spectroscopic methods and gas chromatography in the quantitative and qualitative analysis of medications in the pre-sale procedure testing done in the past ten years. This testing is done as part of the marketing of drugs and their control. During the early stages of its application, high-performance liquid chromatography (HPLC) was expected to be a procedure that would supplement gas chromatography; nevertheless, as of today, HPLC has almost entirely supplanted gas chromatography in the pharmaceutical analysis field. Compared to other methods, utilizing a liquid mobile phase that allows for the transformation of mobilized polarity during chromatography and any other mobile phase modifications that are performed according to the properties of the substance being examined is a significant benefit in the separation process. Furthermore, this instrument has clinical benefits in hospitals. Keywords: HPLC; innovation in health; pharmacy science; laboratory analysis; healthcare technology